Physical and motivational effects of Exergames in healthy adults—A scoping review - Katrin Hoffmann; Josef Wiemeyer; Anna Lisa Martin-Niedecken (PLoS ONE, 2025)
Exergames have the potential to be used as physical-cognitive training tools. Although numerous studies investigated the physical and motivational effects of Exergaming, a comprehensive summary of training effects in healthy adults is still missing. This scoping review aims to identify available evidence and research gaps on absolute and relative effects of Exergame training on physical indicators (effectiveness) and motivation (attractiveness) compared to no or conventional training in healthy adults. A systematic literature search was performed in EBSCOhost, WoS CC, SURF, and Science Research for studies meeting the following criteria: a) randomized controlled trials with Exergames compared to conventional training and/ or no treatment; b) healthy adults (age: 18 to 64 years); c) Exergame training interventions; d) assessment of pre-post differences, primary outcomes: endurance, strength, flexibility, speed, balance, sensorimotor coordination, sports skills, player experience; secondary outcomes: adverse events, physical activity level, attitudes, and knowledge. Methodological quality of included studies was assessed using the PEDro Scale. Charted data were categorized according to the PICOS framework. Mean differences, 95% confidence intervals, and effect sizes (ES) were calculated for continuous outcomes. Evidence Maps were created to illustrate the estimated Risk of Bias, estimated effect, and sample sizes. Eighteen publications with 907 participants were included. The number of studies per outcome was low (2 to 9balance:). Studies on coordination and knowledge were lacking. No study analyzed the relative effects of speed training with Exergames. Absolute effects of Exergame training ranged from no to large effects. Significant ES were consistently found for skill training. Negative effects were found for individual parameters. Relative effects of Exergame training ranged from no to large effects (one exception). A moderate absolute effect favoring traditional training was found for skill training. The remaining results suggest that Exergaming elicited similar training effects compared to conventional training. A high variance of applied training, corresponding training parameters (FITT-VP), outcome measures, as well as methodological deficits and incomplete reporting were identified in included studies. Therefore, a lack of high-quality studies and reviews was identified. Future research should conduct high quality RCT studies analyzing the effectiveness and attractiveness in Exergames. In addition, more suitable, well-designed Exergames should be developed.